2021
DOI: 10.3389/fnagi.2021.657937
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke Anxiety Analysis via Machine Learning Methods

Abstract: Post-stroke anxiety (PSA) has caused wide public concern in recent years, and the study on risk factors analysis and prediction is still an open issue. With the deepening of the research, machine learning has been widely applied to various scenarios and make great achievements increasingly, which brings new approaches to this field. In this paper, 395 patients with acute ischemic stroke are collected and evaluated by anxiety scales (i.e., HADS-A, HAMA, and SAS), hence the patients are divided into anxiety grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Post-stroke mental health disorders, including PSD (17), PSA (18), and PSI (19), are harmful to the quality of life in patients with AIS. Furthermore, these neuropsychological consequences of AIS have adverse effects on functional improvement of AIS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-stroke mental health disorders, including PSD (17), PSA (18), and PSI (19), are harmful to the quality of life in patients with AIS. Furthermore, these neuropsychological consequences of AIS have adverse effects on functional improvement of AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the 9item Patient Health Questionnaire (PHQ-9; range, 0-27) (13), the 7-item Generalized Anxiety Disorder (GAD-7) scale (range, 0-21) ( 14), the 7-item Insomnia Severity Index (ISI; range, 0-28) (15), were used to assess the severity of symptoms of depression, anxiety, and insomnia, respectively. The total scores of these measurement tools were interpreted as follows: PHQ-9, normal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), and severe (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) depression; GAD-7, normal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), and severe (15)(16)(17)(18)(19)(20)(21) anxiety; ISI, normal (0-7), subthreshold (8)(9)(10)(11)(12)(13)(14), moderate (15)(16)(17)(18)(19)(20)(21), and severe (22)…”
Section: Assessment Of Mental Health Outcomesmentioning
confidence: 99%
“…Post-stroke anxiety (PSAn), a consequence of poor motor functioning and substantial decline in quality of life, is a common mental disorder that compromises patient rehabilitation, and, in turn, results in a lasting and steady deterioration of life quality. Previous accumulative studies have reported that PSAn occurs in 18% to 34% of survivors during the first year after stroke, and the rates did not lower meaningfully up to 5 years after stroke [ 59 - 62 ]. Nevertheless, as a serious psychological and physiological problem, PSAn is relatively neglected, presently, compared to other post-stroke psychological disorders.…”
Section: Classification and Clinical Features Of Post-stroke Neuropsy...mentioning
confidence: 99%
“…Most of the developed stroke prediction models are reported in studies on diagnosis, sequela, mortality, and physical function, and cannot be conveniently used practically owing to the associated invasive measurements and analyses 13 16 . Additionally, while studies on predictive model development for stroke-related emotional disorders, such as post-stroke anxiety and PSD have been conducted 17 , 18 , the predictors used in these models were assessed at one-month post-stroke, at which point full depressive symptoms may not be present. Additionally, procedures need to be devised for the comparison of different machine learning models to select the best among them.…”
mentioning
confidence: 99%